Prefrontal attentional saccades explore space rhythmically - Corentin Gaillard (Nature Portfolio, 2020)
The prefrontal attention spotlight dynamically explores space at 7–12 Hz, enhancing sensory encoding and behavior, in the absence of eye movements. This alpha-clocked sampling of space is under top-down control and implements an alternation in exploration and exploitation of the visual environment.